THE IMPORTANCE AND INFLUENCE OF KOKTEBEL IN THE POETIC WORK OF M. VOLOSHIN - Pei Jiamin (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The summary: The article is devoted to the study of the influence of Koktebel on the work of Maximilian Voloshin. The author pays special attention to the poetic heritage of M. A. Voloshin.